The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1158/1535-7163.mct-21-0915
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of IMGC936, a Next-Generation Maytansinoid-based Antibody–drug Conjugate Targeting ADAM9-expressing Tumors

Abstract: A disintegrin and metalloprotease (ADAM) 9 is a member of the ADAM family of multifunctional, multidomain type 1 transmembrane proteins. ADAM9 is overexpressed in many cancers, including non-small cell lung, pancreatic, gastric, breast, ovarian, and colorectal cancer, but exhibits limited expression in normal tissues. A target-unbiased discovery platform based on intact tumor and progenitor cell immunizations, followed by an immunohistochemistry screen, led to the identification of anti-ADAM9 antibodies with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Recently, other than YTE and LS mutations, several mutations to increase FcRn binding have been reported and evaluated in preclinical and clinical studies [29][30][31]. Also, YTE mutations were reported to be applied in ADC [32] and Fc-fusion protein [33] to prolong half-life. The optimized allometric scaling approach could be widely used for mAbs and other therapeutic modalities which contain mutations to increase FcRn binding and can contribute to the efficient development of such therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other than YTE and LS mutations, several mutations to increase FcRn binding have been reported and evaluated in preclinical and clinical studies [29][30][31]. Also, YTE mutations were reported to be applied in ADC [32] and Fc-fusion protein [33] to prolong half-life. The optimized allometric scaling approach could be widely used for mAbs and other therapeutic modalities which contain mutations to increase FcRn binding and can contribute to the efficient development of such therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…As determined by a literature search of PubMed and ClinicalTrials.gov, two clinical trials targeting ADAMs are ongoing as of August 2022. The first is a first-in-human study of IMGC936 in patients with advanced solid tumors (NCT04622774) [ 115 ]. IMGC936 is a novel antibody–drug conjugate targeted against ADAM9 and comprises a high-affinity humanized antibody site.…”
Section: Adams As Immunotherapeutic Targetsmentioning
confidence: 99%
“…IMGC936 is a novel antibody–drug conjugate targeted against ADAM9 and comprises a high-affinity humanized antibody site. As preclinical data, Scribner et al reported that IMGC936 exhibits cytotoxicity in ADAM9-positive human tumor cell lines, along with bystander killing and potent antitumor activity in xenografts derived from tumors and human tumor cell lines [ 115 ]. A clinical trial combining an antibody-drug conjugate and immunotherapy is near at hand.…”
Section: Adams As Immunotherapeutic Targetsmentioning
confidence: 99%
“…A disintegrin and metalloproteinase domain-containing protein 9 (ADAM9) is a member of the ADAM family of transmembrane proteins belonging to the zinc protease superfamily. ADAM9 physiologically regulates cell adhesion and intracellular signal transduction in several malignant tumors [ 11 , 12 , 13 , 14 ]. In bladder and prostate cancers, knockdown of ADAM9 suppresses cancer cell proliferation [ 15 , 16 ] and inhibits cancer cell migration by suppressing epithelial–mesenchymal transition (EMT), which is related to cancer progression and metastasis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%